2017
DOI: 10.1002/2017ja024422
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Sunward Propagating Alfvénic Fluctuations With a Power Law Spectrum Observed by the Wind Spacecraft

Abstract: Sunward propagating Alfvénic fluctuations with a power law spectrum (SAFP) have been recently observed in the upstream region of the Earth's bow shock. However, some physical properties of these fluctuations such as anisotropy remain unclear. Here we develop a new method for identifying SAFPs, and present for the first time the anisotropy of SAFPs power and spectral index. In this method, the propagation direction determination of SAFPs does not rely on a radial magnetic geometry but the pitch angle distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The above works support the idea that switchbacks are localized twists in the magnetic field and not polarity reversals. Wu et al (2017) identified localized twists based on the combination of the propagating direction of the fluctuations and the pitch angle of strahl electrons using WIND measurements at 1 au, suggesting that local twist switchbacks exist up to 1 au. The nature and the formation of the switchbacks are important to understand the evolution of solar wind in the inner heliosphere (Macneil et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The above works support the idea that switchbacks are localized twists in the magnetic field and not polarity reversals. Wu et al (2017) identified localized twists based on the combination of the propagating direction of the fluctuations and the pitch angle of strahl electrons using WIND measurements at 1 au, suggesting that local twist switchbacks exist up to 1 au. The nature and the formation of the switchbacks are important to understand the evolution of solar wind in the inner heliosphere (Macneil et al 2020).…”
Section: Introductionmentioning
confidence: 99%